2022
DOI: 10.3390/molecules27134027
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Catechol-Containing Polyacrylamides with Adhesive Properties

Abstract: In this study, a row of four analogous dopamine acryl- and methacrylamide derivatives, namely N-(3,4-dihydroxyphenyethyl) acrylamide, N-(3,4-dihydroxyphenyethyl) meth acrylamide, N-phenethyl methacrylamide, N-(4-hydroxyphenethyl) methacrylamide were synthesized and characterized by 1H-NMR and 13C-NMR, followed by further solvent-based radical polymerization with N-hydroxyethyl acrylamide. All copolymers were characterized by 1H-NMR, dynamic differential calorimetry, and gel permeation chromatography. The depen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…We focus on free radical polymerization, which is often preferred for larger scale synthesis and applications. Various studies showed the feasibility of free and controlled radical polymerization routes toward uncharged [ 43 , 44 , 45 , 46 , 47 ] and charged [ 24 , 30 , 34 , 35 ] catechol-containing copolymers. Importantly, however, the effect of additional primary amide units was not yet studied in such copolymer systems.…”
Section: Introductionmentioning
confidence: 99%
“…We focus on free radical polymerization, which is often preferred for larger scale synthesis and applications. Various studies showed the feasibility of free and controlled radical polymerization routes toward uncharged [ 43 , 44 , 45 , 46 , 47 ] and charged [ 24 , 30 , 34 , 35 ] catechol-containing copolymers. Importantly, however, the effect of additional primary amide units was not yet studied in such copolymer systems.…”
Section: Introductionmentioning
confidence: 99%
“…Surface modification of materials using molecules from the catechol family is emerging as a new area of technological and scientific interest [ 1 , 2 ]. Catecholate molecules can achieve extremely strong adhesion to inorganic surfaces by utilizing a similar adsorption mechanism to that of mussel proteins when bonded to different surfaces [ 2 , 3 , 4 ]. Very fast and very strong adsorption to various inorganic substrates is a necessity for mussels to avoid damage by sea waves.…”
Section: Introductionmentioning
confidence: 99%
“…Very fast and very strong adsorption to various inorganic substrates is a necessity for mussels to avoid damage by sea waves. This adhesion mechanism is attributed to bonding of the catechol ligands of the mussel proteins to metal atoms on material surfaces [ 4 , 5 , 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation